Water Dynamics in Competitive Solvation Assisted Loading of Colloidal Curcumin Nanoparticles onto Mesoporous Silica Nanostructures. (1st July 2022) - Ananth, A. Nitthin; Nagarajan, V.; Kumar, S. Suresh; Sasikumar, P.; Chirico, Giuseppe; D'Alfonso, Laura; Jose, Sujin P.
Abstract: The main goal of this study is to develop methods for the simultaneous synthesis and loading of curcumin nanoparticles onto mesoporous silica by a sequential solvent evaporation approach. It is known that the presence of cosolvents and surfactants facilitates the homogenous formation of colloidal curcumin nanoparticles and enhances loading into mesoporous silica nanoparticles. The stability of the curcumin nanoparticles and their substantial loading are characterized as a function of the mesoporous silica nanostructures (MSN) surface properties, allowing to put into evidence how the dielectric nanoenvironment, largely determined by the water dynamics in the presence of cosolvents and of surfactants, plays a crucial role in the micelle mediated loading of curcumin nanoparticles into the mesoporous silica nanostructure. The interfacial hydrogen bonded corrugated network with its occupational electronic distribution shields the curcumin nanoparticles loaded onto the MSNs. Highly monodispersed nanostructures that are obtained that exhibit redox behavior, Fickian diffusion following linear compensation effect, and increased ionic activity triggered in an acidic pH ambiance. The augmented bioactivity of the human acute monocyte leukemia cancer cell line U937 elects the synthesized curcumin nanoparticles @ MSNs as a suitable nanostructure against acidic tumor microenvironment. Abstract : Sequential solvent evaporation in loading the colloidal curcumin nanoparticles onto the mesoporous silica nanostructures (CR@MSNs) – one‐pot approach is formulated. Interaction of the solvents in the reduction and loading of curcumin nanoparticles and the competitive water dynamics along with the cosolvents is investigated with computational support. The solvents of different dielectric permittivity significantly augment the properties of the bioactive CR@MSNs.